End-winding effect on shaft voltage in AC generators - Abadi, J.; zare, F.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
This paper presents effects of end-winding on shaft voltage in AC generators. A variety of design parameters have been considered to calculate the parasitic capacitive couplings in the machine structure with Finite Elements simulations and mathematical calculations. End-winding capacitances have also been calculated to have a precise estimation of shaft voltage and its relationship with design parameters in AC generators.